The policy of integrated languages didactics in Lithuania - Daiva Jakavonytė-Staškuvienė (Problemy Wczesnej Edukacji)
The article analyses the policy, theory and research-based practice of integrated languages didactics. It discusses teaching quality, determining factors, the role of integrated languages didactics, its challenges and sensitive aspects in organising integral learning. The development of learning curriculum (depending on the context) and reflection activities are the key element in establishing quality-focused integrated learning practices.